A Clinical Case Report: Artery-Veins Congenital Malformation - Buque, Amelia; Hussain, Rameez (European Journal of Applied Sciences, 2023)
Aim: To report a clinical case of 10 years old girl, with low visual acuity in her right eye. Methods: This case report is a retrospective and descriptive study. Data was gathered from patient clinical record file that included anamnesis, examination and analysis of diagnostic tests. Results: A 10 years old female complains of headache, blurry visual acuity in her right eye (RE), for the last two weeks, before consultation. Uncorrected visual acuity RE was 6/9 and 6/6 in the left. Best corrected vision 6/6 for the both eyes. Both eyes anterior segment examination was normal. Right eye posterior segment exam revealed optical disc, tortuous artery-veins. The posterior segment of the left eye reveled normal. The OCT (Optical Coherence tomography) angiography showed dilated and tortuous vessels visible. Left eye OCT angiography reveled normal. The brain magnetic resonance imaging did not reveal any other arteriovenous malformation. Conclusion: On dilated fundus examination, a 10-year-old girl’s right eye revealed markedly dilated and tortuous vessels arising from the disc suggestive of Wyburn-Mason Syndrome of the right eye. This is a rare